Pengaruh Intensitas Aset Biologis, Ukuran Perusahaan, Dan Kualitas Audit Terhadap Pengungkapan Aset Biologis (International Forum of Researchers and Lecturers, 2023)
The finance position describes the company’s position so that it can assist in analyzing the company’s performance. Biological asset accounting policies must be presented so that interested parties can understand the performance of biological assets. This study aims to determine the effect of biological asset intensity, company size, and audit quality on the disclosure of biological assets. The result of this study indicate that the variables of biological asset intensity and company size have a significant positive effect on the disclosure of biological assets while audit quality has no effect on the disclosure of biological assets.